Coping With Food Insecurity Using the Sociotype Ecological Framework - Peng, Wen; Dernini, Sandro; Berry, Elliot M. (Frontiers in Nutrition, 2018)
Ensuring Food Security (FS) for all citizens is a fundamental human right and policy for all countries. Dealing with FINS is a challenge causing stress at many levels – national, household and individual. The conceptual framework of the Sociotype has been developed as a summary ecological construct to organize the multiple, dynamic, reciprocal inputs from the environment that interact with the genotype to determine the expression of phenotypic behaviors such as coping with stress. The Sociotype ecological framework has three domains – Individual (intra-personal), Relationships (inter-personal, family and community) and Context (environment, national) – and their interactions determine an individual’s resilience across the life trajectory from birth to old age. We have applied the principles of the Sociotype to classify both the stresses of, and the coping strategies to, FINS. The stresses of FINS may occur at any place along the FS pathway – Availability, Accessibility, Utilization and Stability. The elicited coping responses may take place in one or more of the three Sociotype domains. The two processes are inter-related linearly with re-iterative feedback loops such that stress leads to coping responses that may or may not be adequate, thereby requiring modifications in the coping strategies until FS is regained. Resilience is considered to represent long-term coping strategies. The Sociotype framework is both a determinant of, and constant input to, building and strengthening resilience. However, the people with the most problems with FINS are rarely included in these discussions. They are the marginalized members of society: unemployed, homeless, displaced persons, special needs, elderly, single parents, mentally frail and more. Applying the Sociotype ecological framework for coping with FINS stresses can allow better strategic planning for FS at national, household and individual levels and understanding the interactions between them to reach out to and help these sectors of the population.